Applicability Evaluation of TRMM Satellite Precipitation Data in Jiangsu Province - XU Shanshan (Renmin Zhujiang)
According to the measured data of 167 rainfall stations in Jiangsu Province from 2000 to 2013,the feasibility of the application of TRMM satellite precipitation data (TRMM 3B42 daily precipitation products and TRMM 3B43 monthly precipitation products) in Jiangsu Province is tested and discussed at multiple scales.On the multi-year average scale,the spatial distribution of TRMM precipitation data and measured precipitation data are decreasing from south to north,but the precipitation value of TRMM is higher than the measured one.On the daily scale,the coincidence degree between TRMM 3B42 precipitation data and measured precipitation data is tested by precipitation frequency,missing and empty retrieval rates,and precipitation classification.The missing and empty retrieval rates of Lianyungang and Suqian are lower,thus,in the two places,TRMM inversion data are more accurate to distinguish whether there is precipitation in the actual situation.The relative error of TRMM 3B42 data for measuring light rain is relatively large,while it is small for medium rain,heavy rain,and rainstorm.On the monthly scale,it can be seen that the consistency between TRMM 3B43 data and ground data is overall high by examining the correlation coefficient and the absolute error.The correlation coefficient is the highest in Xuzhou and the north of Lianyungang but slightly lower in the south of Jiangsu and surrounding areas of Hongze Lake.On the annual scale,the variation coefficients between the measured precipitation data and the TRMM precipitation data are compared,and they show the same law that the fluctuation of precipitation is small in the south of Jiangsu but large in the north.